LEGAL AND REGULATORY FRAMEWORK OF PSYCHOLOGICAL REHABILITATION FOR ANTITERRORIST OPERATION PARTICIPANTS - Havlovskyi, O.D.; Holovanova, I.A.; Ovcharenko, O.M. (World of Medicine and Biology, 2019)
Psychological rehabilitation is a very significant issue not only for the participants of antiterrorist operation (further – ATO), but also for the whole society. Nevertheless, due to the specific character of the problem in question for all Ukrainians, it is not fully researched at the current time. The article attempts a scientific and theoretical analysis of the legal and regulatory framework of psychological rehabilitation for ATO participants. The paper provides the analysis as well as the systematization of the principal legal acts which regulate the issues of rehabilitation for the participants of ATO. The sum-total of the analyzed legal and regulatory acts, connected with the psychological rehabilitation for ATO participants, can be grouped according to the legal force and the subject of enactment. Such acts form the legal mechanism of state administration by the specified social conventions. The results of the research showed that the legal and regulatory framework of psychological rehabilitation does not correspond to contemporary needs, as well as it does not agree with the international norms and standards. It is necessary to improve and bring up to date the legal system in the sphere of psychological rehabilitation that will favour the improvement of its organization and will optimize the mechanism as well as the procedure of making decisions in the sphere. Such measures will benefit the decrease of the state budget expenditures and will enhance the efficiency of providing the rehabilitation service.